Steindl on imperfect competition: The role of technical change - Bloch, Harry (Blackwell Publishing Ltd, 2006)
Josef Steindl offers an innovative dynamic analysis of competition in Maturity and Stagnation in American Capitalism, with a key role for technical change. However, in his later writings he suggests that he had not gone far enough and that his account was not 'sufficiently dynamic', noting particularly his neglect of fundamental issues in technological development. Here, we critically examine the nature of technical change in Steindl's analysis, pointing to ambiguities and contradictions that arise. Standard characterizations of the nature of technical change are then introduced and used to further integrate technical change into Steindl's analysis of competition.